The 2022 Ethiopia’s first-ever national dialogue formation: analyzing challenges and prospects - Mersha Zenebe Felek (Cogent Social Sciences)
Ethiopia held its first national dialogue in response to historical and present issues. This study critically explored the opportunities and challenges of Ethiopia’s present national dialogue. To this end, both the primary and secondary data were collected. To collect primary data, focus group discussions and semi-structured interviews were conducted with representatives of various political parties and key informants. Books, articles, reports, and news are examples of secondary data used in this study. As a result of the findings of this research, the prospects include the development of the Ethiopian National Discussion Commission, the release of political prisoners, favorable reactions to the importance of national discussion, and Ethiopian religion and cohesion. On the other hand, the study explained that the controversy surrounding the establishment of Ethiopian national dialogue, the reduced inclusiveness of the national dialogue process, conflict with the TPLF and Shene, the inclusion of the TPLF and Shene as terrorists by the Ethiopian parliament, a lack of good governance, political polarization (centripetal and centrifugal forces), and imperial syndrome are all posing challenges to the current Ethiopian national dialogue. Overall, despite the major hurdles, the national conversation initiative has a high chance of uniting Ethiopians. Finally, the report recommended that the Ethiopian National Dialogue Commission draft a clear activity plan and begin its implementation as soon as possible.